A Study of the safety program of the manufacturing division of the Atlantic Gulf and Pacific Co., Inc. - Enriquez, Florencia; Esguerra, Alfonso; Johnson, Joseph; Sales, Argeo; Villena, Dominador; Lim, Francisco (Diliman, Quezon City College of Engineering, 1971)
Any study is not of value unless recommendations are made to correct existing defects present in any system. In this study of the safety program of the Manufacturing Division of AG&P, the group have made recommendations, some of which need immediate attention from management, while some do not. Although the group recognizes and appreciates the existing well-defined and integrated safety program of the company, we cannot set aside the fact that defects are in existence. A summary of the more immediate recommendations we have made are listed below : 1) a more rigid implementation of company safety rules and regulations, 2) improvement of ventilation in the plant, 3) guarding of all unguarded machineries, 4) a more improved procedure in the safekeeping of safety equipments.
Feasibility study
Keywords: Atlantic Gulf and Pacific Co. Incorporated; Manufacturing industries